Institutional theory in Political Science : the new institutionalism - Peters, B. Guy (New York, 2012)
This completely revised edition offers a comprehensive treatment of institutional theory in contemporary political science. "Institutional Theory in Political Science" provides an in-depth analysis of contemporary institutional theory, an essential tool to understand the world of politics and government. Written by B. Guy Peters, a prominent expert in the field, the book argues that the new institutionalism comprises eight variations on the theme of institutional analysis. Through a series of questions, the author assesses the possibility of a unified theory within institutionalism and its potential as a paradigm for political science. This new edition incorporates the most recent developments in the research on the various institutionalisms. It also includes a new chapter that brings into the discussion themes of discursive politics and constructivism. Although the focus is on political science, attention is paid to institutionalism in other disciplines. "Institutional Theory in Political Science, 3rd Edition", reflects the state of the field today while building on the foundations set in the previous editions. This unique work will be of value to anyone studying institutionalism, as well as political institutions, and public administration.
Keywords: Institutionalism